ANALISIS PERTIMBANGAN HUKUM HAKIM MAHKAMAH AGUNG DALAM PENINJAUAN KEMBALI PUTUSAN NOMOR 1332/PK/Pdt/2022 - NIM. A1012181229, RAPHAEL TJONDRO (Jurnal Fatwa Hukum, 2025)
Abstract  The Plaintiff's lawsuit is basically based on the Plaintiff's argument that he already had a certificate first, namely the Land Use Rights Certificate Number 7/Kuala Dua Village, dated September 15, 1995, Situation Drawing (GS) Number 5/1993 Plot A, dated May 31, 1993, area 20.1870 last recorded in the name of the rights holder Yayasan Panca Bhakti; Land Use Rights Certificate Number 8/Kuala Dua Village, dated September 15, 1995, Situation Drawing (GS) Number 5/1993 Plot B, dated May 31, 1993, area 20.1783 ha (twenty point one seven eight three hectares), last recorded in the name of the rights holder Yayasan Panca Bhakti; and Certificate of Ownership Number 1446/Kuala Dua Village, dated April 12, 2001, Measurement Letter (SU) Number 73/2000, dated January 20, 2001, area 19,950 m ² as the object of the dispute over issuing three certificates is an act that is contrary to applicable laws and regulations and the principles of good governance, especially the principle of formal accuracy.The purpose of this study is to analyze the legal considerations of the Supreme Court judge in obtaining a judicial review of decision number 1332/pk/pdt/2022 concerning the right to cultivate disputes and to analyze the legal consequences of the judicial review decision in case number: 1332/pk/pdt/2022 concerning the right to cultivate disputes.In conducting this research, the author uses the normative legal research method. It is concluded that the Consideration of the Pontianak State Administrative Court Judge That regarding the reasons of the Applicant for Judicial Review regarding the existence of new evidence that is decisive, so that there is no conflict between the two decisions that have permanent legal force, therefore as long as the building use rights certificate and the Ownership Rights Certificate owned by Defendants I and II are not canceled and are not declared invalid by the authorized institution, then the proof of ownership remains valid, and the Respondent for Judicial Review 1 has filed a counter memorandum for judicial review dated September 20, 2022 which rejects the judicial review application from the Applicants for Judicial Review.Keywords: Supreme Court, Judicial Review, Cultivation Use Rights  Abstrak  Gugatan Penggugat pada pokoknya berdasarkan dalil Penggugat telah memiliki sertifikat terlebih dahulu yakni Sertipikat Hak Guna Usaha Nomor 7/Desa Kuala Dua, tanggal 15 September 1995, Gambar Situasi (GS) Nomor 5/1993 Persil A, tanggal   31   Mei   1993,   luas   20,1870   terakhir tercatat atas nama pemegang hak Yayasan Panca Bhakti; Sertipikat Hak Guna Usaha Nomor 8/Desa Kuala Dua, tanggal 15 September 1995, Gambar Situasi (GS) Nomor 5/1993 Persil B, tanggal 31 Mei 1993, luas 20,1783 ha (dua puluh koma satu tujuh delapan   tiga hektar),   terakhir tercatat   atas nama pemegang   hak Yayasan Panca Bhakti; dan Sertipikat Hak Milik Nomor 1446/Desa Kuala Dua, tanggal 12 April 2001, Surat Ukur (SU) Nomor 73/2000, tanggal 20 Januari 2001, luas   19.950   m ² sebagai obyek sengketa atas menerbitkan tiga sertifikat merupakan perbuatan yang bertentangan dengan peraturan perundangan yang berlaku dan asas pemerintahan yang baik khususnya asas kecermatan formal.Adapun yang menjadi tujuan dari penelitian ini adalah untuk menganalisis pertimbangan hukum hakim mahkamah agung dalam perolehan peninjauan kembali putusan nomor 1332/pk/pdt/2022 tentang sngketa hak guna usaha dan untuk menganalisis akibat hukum putusan peninjauan kembali   perkara nomor: 1332/pk/pdt/2022 tentang sngketa hak guna usaha.Dalam melakukan penelitian ini penulis menggunakan metode penelitian hukum normatif.Maka disimpulkan bahwa Pertimbangan Hakim Pengadilan Tata Usaha Negara Pontianak Bahwa terhadap alasan-alasan dari Pemohon   Peninjauan Kembali tentang adanya bukti baru yang   menentukan,   sehingga   tidak   terdapat pertentangan   antara kedua putusan yang telah berkekuatan   hukum tetap, oleh     karena     sepanjang     sertipikat     hak     guna     bangunan     dan Sertipikat Hak Milik yang dimiliki oleh Para Tergugat I dan II tidak dibatalkan dan tidak dinyatakan tidak sah oleh lembaga yang berwenang, maka bukti kepemilikan mana tetap sah, dan Termohon     Peninjauan     Kembali     1     telah     mengajukan     kontra     memori peninjauan kembali tanggal 20 September 2022 yang menolak permohonan peninjauan kembali dari Para Pemohon Peninjauan Kembali.Kata Kunci : Mahkamah Agung, Peninjauan Kembali, Hak Guna Usaha